Effect of educational curriculum on coordination and learning of forward and backward rolls on floor mats in female artistic gymnastics - Finteel , Ali Kareem; Kadhem, Abbas Abdulhamza; Hussien, Abeer Ali (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of the present study was to prepare an educational curriculum to improve coordination and learning of forward and backward rolls on floor mats in female artistic gymnastics. The present study had an experimental design. Students of the second stage of the College of Physical Education and Sports Sciences of the University of Karbala (academic year 2020-2021) constituted the research community for the present study. A total of 54 students, present in the research community, were recruited as the participants of the study. Participants were allocated into two groups, experimental group and control group, by simple random allocation method. Based on the findings of the present study, the researchers concluded that the educational curriculum improved the coordination and learning of forward and backward rolls on floor mats.